Pengembangan Pengembangan E-Modul Peninggalan Sejarah Kolonialisme Belanda di Bengkulu pada Pembelajaran Tematik Terpadu Kelas V di Sekolah Dasar: Pengembangan E-Modul Peninggalan Sejarah Kolonialisme Belanda di Bengkulu pada Pembelajaran Tematik Terpadu Kelas V di Sekolah Dasar - Mufidah Mahdiyah Mahdiyah; Pebrian Tarmizi; Panut Setiono (JURIDIKDAS, 2022)
This study aims to develop an e-module learning media of the Dutch colonialism history in Bengkulu at an integrated thematic learning fifth-grade elementary school. The research type was "research and development" (R&D) with the ASSURE model. The instruments used were product validation sheets, teacher response questionnaires, and student response questionnaires. The data analysis technique used descriptive statistical analysis of the results of the expert validation assessments, teacher responses, and student responses and qualitative descriptive analysis of the comments from the experts’ validation assessments, teacher responses, and students’ responses. The results of the material expert validation showed a score of 92%, and the media expert validation showed a score of 97.5% with a very valid category. The teacher's response showed a score of 89%, and the students' responses showed a score of 94.33%. The overall results showed that the e-module learning media for the Dutch colonialism history in Bengkulu is very valid and adequate for use in learning.